Pengelolaan Obat High Alert, LASA (Look-Alike Sound-Alike), Emergensi, dan Obat Umum di Farmasi RSUP Fatmawati - Suaif, Suaif (RSUP Fatmawati, 2025)
Proper management of drug storage in hospitals is essential for ensuring quality and patient safety, particularly for high-alert drugs, look-alike sound-alike (LASA) drugs, and emergency drugs. This study evaluates the storage system for these drugs in the Fatmawati Hospital Pharmacy Warehouse according to the PKPO and SKP standards established by the Indonesian Ministry of Health. The evaluation was conducted through direct observation, a document study, and a comparison to Permenkes and Kepmenkes standards. The results show that, while most of the storage system is appropriate, there are still non-conformities, such as high-alert drugs being placed outside the red zone, suboptimal LASA marking, and limited warehouse space. The study recommended improvements to the marking zone, staff training, and layout arrangements. The results showed that 94% of high-alert drug storage was in the excellent category, 70% of LASA drug storage was in the good category, 80% of trolley emergency drug storage was in the good category, and 85.14% of general drug storage was in the good category. Statistical analysis using a t-test revealed that the storage of high-alert, LASA, emergency, and general drugs had a significance value of p > 0.05. These results illustrate that drug storage in the Fatmawati Hospital Pharmacy warehouse meets the standards. Keywords: Medication Storage, High-Alert Medications, LASA, Emergency Medications, Pharmaceutical Warehouse.